2007
DOI: 10.1200/jco.2007.11.2243
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Toxicity Monitoring via Electronic Patient-Reported Outcomes in Patients Receiving Chemotherapy

Abstract: Online patient self-reporting is a feasible long-term strategy for toxicity symptom monitoring during chemotherapy, even among patients with advanced cancer and high symptom burdens. However, without explicit reminders and clinician feedback, patients demonstrated limited voluntary interest in self-reporting between visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
200
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(208 citation statements)
references
References 18 publications
8
200
0
Order By: Relevance
“…We identified possible ADEs from the Common Terminology Criteria for Adverse Events version 4.0 [22], and existing symptom and ADE checklists [3,13,18,[23][24][25][26][27][28][29]. Patient-reported data about ADEs from the Lareb Intensive Monitoring System of The Netherlands Pharmacovigilance Centre Lareb [30] were used to translate ADEs into lay-terms.…”
Section: Adverse Drug Event (Ade) Selection and Naming In Lay-termsmentioning
confidence: 99%
“…We identified possible ADEs from the Common Terminology Criteria for Adverse Events version 4.0 [22], and existing symptom and ADE checklists [3,13,18,[23][24][25][26][27][28][29]. Patient-reported data about ADEs from the Lareb Intensive Monitoring System of The Netherlands Pharmacovigilance Centre Lareb [30] were used to translate ADEs into lay-terms.…”
Section: Adverse Drug Event (Ade) Selection and Naming In Lay-termsmentioning
confidence: 99%
“…This has been identified as a problem in other research whereby poor utilisation of symptom reporting was associated with a perception among the participants that the information was not being explicitly addressed by the clinicians (Basch et al, 2007). A prerequisite to patient utilisation of an intervention in clinical practice is the perception that the intervention is of interest or can be used by the clinicians involved in that patient's care.…”
Section: Utilisation Of Diarymentioning
confidence: 95%
“…This is not unusual when implementing a new tool into routine practice (Lecouturier et al, 2002) and a similar study that implemented electronic recording of symptoms at chemotherapy clinics found that the most common barrier to adherence was that staff failed to remind patients to use the system (Basch et al, 2007). Although both community and hospital staff were aware that this study was ongoing and that patients had diaries which they were encouraged to share with them, it was not stipulated that they should ask patients for their diary.…”
Section: Utilisation Of Diarymentioning
confidence: 99%
“…There are several advantages of ePRO, such as rapid access to data, a probable avoidance of errors during data entry, and fewer missing data in comparison with paperbased surveys and the capacity to trigger alerts or notifications for answers to special circumstances 3 and an improvement in patients' willingness to report sensitive information [23,28]. Although paperbased surveys of PRO still predominate because there are only a few reliable and validated ePRO questionnaires, numerous projects have evaluated feasibility and acceptance of HRQoL in ePRO measurement in the last few years [29][30][31][32][33][34]. Nevertheless, knowledge regarding patient acceptance, feasibility, and barriers remains limited [35], especially since hurdles might exist in relation to health status, technical skills, and socioeconomic aspects, which could influence both patients´ willingness to use ePRO and their response behavior [10,36,37].…”
Section: Electronic Measurement Of Patient-reported Outcomesmentioning
confidence: 99%